Analisis Perbandingan Sistem Administrasi Negara Indonesia Dengan Sistem Administrasi Negara China - Nur Jannah, Nurisma Rizky; Kamila, Oktaviani Cahya (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2025)
This study aims to analyze the differences and similarities between the public administration systems of Indonesia and China by focusing on four key aspects: public service quality, political system, global competitiveness, and bureaucratic performance. The research adopts a literature review method by examining various academic sources, including scholarly journals and official policy documents. The findings reveal that Indonesia, although adopting a democratic system with high public participation, still faces challenges in service delivery efficiency, bureaucratic productivity, and fragmented policymaking. Meanwhile, China, under a centralized governance system, has successfully implemented comprehensive bureaucratic reforms, strengthened public services through digital transformation, and demonstrated high global competitiveness. The study concludes that despite fundamental differences in administrative and political structures, both countries have valuable insights to offer. Indonesia may adopt China’s bureaucratic efficiency strategies, provided they are adapted to the democratic and participatory context of the country.